2018
DOI: 10.23822/eurannaci.1764-1489.28
|View full text |Cite
|
Sign up to set email alerts
|

Bodybuilding protein supplements and cow’s milk allergy in adult

Abstract: Summary We report a case of a previously healthy 24-year-old man with a 3-month history of gastrointestinal symptoms during exercise and also few minutes after the ingestion of cow's milk (CMBodybuilding protein supplements and cow's milk allergy in adult Previous presentationThe data reported in this study was presented by Maria João Sousa (co-authors: Ferreira AR, Moreira Silva JP) at the EAACI Congress 2015 in Barcelona (Spain) 6-10 June 2015, as a poster entitled "Adult-onset cow's milk allergy and Bodybui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The main task of a data mining application is to locate and explain the problems that need to be solved. In addition to choosing a suitable extraction method, the target details should also be detailed and clear in order to study the impact of data extraction and the effectiveness of the model creation [ 13 ].…”
Section: Data Mining Technology and Fitness And Bodybuilding Exercise...mentioning
confidence: 99%
“…The main task of a data mining application is to locate and explain the problems that need to be solved. In addition to choosing a suitable extraction method, the target details should also be detailed and clear in order to study the impact of data extraction and the effectiveness of the model creation [ 13 ].…”
Section: Data Mining Technology and Fitness And Bodybuilding Exercise...mentioning
confidence: 99%
“…A risk factor for developing CMPA in adulthood is the excessive intake of dairy products[ 57 ]. Sousa et al [ 58 ] reported a 24-year-old man who developed CMPA after excessive intake of hydrolyzed casein and whey CMPs for bodybuilding for two years. CMPA was confirmed by positive IgE against cow’s milk α-lactalbumin, β-lactoglobulin, and casein extracts, suggesting that excessive CM intake may induce CMPA.…”
Section: Cow’s Milk Protein Allergymentioning
confidence: 99%
“…CMPA was confirmed by positive IgE against cow’s milk α-lactalbumin, β-lactoglobulin, and casein extracts, suggesting that excessive CM intake may induce CMPA. On the other hand, adult patients with CMPA have lower IgG levels than controls[ 58 ]. The respiratory tract and skin are the main organs affected in adulthood CMPA in adults, while gastrointestinal and cardiovascular manifestations are less frequent than in childhood CMPA[ 59 ].…”
Section: Cow’s Milk Protein Allergymentioning
confidence: 99%